PENENTUAN PRIORITAS PENINGKATAN LAYANAN PENERANGAN JALAN UMUM DI KOTA KEDIRI - Christiawan, Jimmy Septian; Basuki, Yudi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
Kediri city has a role as a Regional Development Centre for the region around it. The role focuses on the trade in goods and services, industry and education. The impact is an increase in urban activity, including in the transportation sector. The existence of street lights as part of road complementary facilities has an important function in supporting road user safety and improving the city's economy. However, street lighting services in Kediri City do not meet the minimum standards required. So that an increase in street lighting services is absolutely necessary. The limited available resources make it difficult for the Kediri City Government to improve overall street lighting services. Based on these problems, this study aims to determine the priority of improving street lighting services in Kediri City. This research use mix method, namely use the qualitative and quantitative approachment, using the Analytical Hierarchy Process (AHP) and weighted overlay as analytical tools. AHP is used to determine the weight of each variable for priority setting. Weighted overlay analysis is used to determine the priority of road lights improvement by combining the weight variables of AHP results and variable values on each road segment. The AHP produced the highest weight in planning for increasing street lighting was the accident hazard rate (16%) and the number of intersections (12.49%). The final analysis produces four priority levels. The main priorities are on the Kapten Tendean and K.H.Ahmad Dahlan road sectionsÂ